Fishery and estimation of Potential yield for Bombayduck Harpodon nehereus along Gujarat coast, India - Vase, Vinaya Kumar; Kumar, Rajan; Nakwa, A. D.; Rahangdale, Shikha; Jayasankar, J.; Mohammed Koya, K.; Divu, D.; Rohit, Prathibha (Indian Journal of Fisheries, 2020)
Bombayduck Harpadon nehereus (Hamilton, 1822) is one of the key fishery resources landed along the Indian coast with uniqueness in distribution and exploitation. The resource is known for discontinuous distribution, majorly along the north-west and north-east coasts of India. Gujarat is the lead state to contribute nearly 64.72% (72,949 t) to the total national landings of the resource (11,2705 t) in 2018. Dolnet gear contributes nearly 95% of the total landings of the resource in the region. The landings and the corresponding catch per unit effort (CPUE) showed a fluctuating trend over the study period of 1994-2014. The catches fluctuated between 35,235 t (2016) and 92,188 t (2004), whereas the CPUE oscillated in the range of 15 to 20 kg h-1 (1998) and 30.76 kg h-1 (2003). The period of 1994-2000 was the most productive period with an average catch of 72,133 t, whereas the succeeding decade was the leanest phase with an average annual catch of 50,035 t. The estimated potential yield (= maximum sustainable yield, MSY) was estimated at 73,700 t and 70,108 t using the Bayesian surplus production model (CMSY & BSM) and basic Schaefer surplus production model respectively. The present catch and exploitation levels were found to be close to the optimum level and a further increase in effort for the resource is not recommended.Keywords: Bombayduck, BSM, CMSY, Harpadon nehereus, Median catch, Surplus production model